Research of stability of geometric parameters of wood under the moisture action - Yaris, Vadim; Ved, Viktor; Zybaylo, Sergiy; Chaban, Oleh; Karpenko, Veronika (Technology audit and production reserves, 2020)
The object of research is a promising structural material – modified wood. Extending the use of wood while maintaining structural characteristics is a promising area of research. Modification of wood in accordance with structural requirements, taking into account sanitary and other requirements, is an important task. The most common modification technologies are impregnation. Pressure autoclaving wood requires sophisticated equipment to create unprofitable pressure. Impregnation by the condensation method or the method of «cold and hot baths» significantly reduces the cost of obtaining modified wood. The study of the stability of the geometric dimensions of modified wood under the moisture influence makes it possible to evaluate the effectiveness of the modification (impregnation) process and, as a result, evaluate the service life. Samples from pine timber (DSTU ISO 738:2018) with a size of 300–70–15 mm are used. For research, three groups of samples are selected with radial (R), tangential (T) and mixed (M) direction of wood fibers. For impregnation modification, linseed oil and drying oil were used at a concentration of 25 g/l. In accordance with the modification technology, the samples are soaked in an aqueous solution with a desiccant, then immersed in linseed oil heated to 130±10 °С, and then immersed in linseed oil at a temperature of 20 °С. The obtained samples are dried under atmospheric conditions and soaked in water for 24 hours to study the stability of geometric dimensions. As a result of studies, it is found that the optimal temperature for heating the samples is the range 120–140 °C. It is also found that the most resistant to changes in geometric dimensions are samples with a mixed direction of the fibers (M), in which size changes are 0.5 % compared to dry samples. Regardless of the direction of the fibers, the moisture absorption of the modified samples is 0.07 vol. %, which is of great practical interest.